2021
DOI: 10.3390/app11062704
|View full text |Cite
|
Sign up to set email alerts
|

Interoperability Reference Models for Applications of Artificial Intelligence in Medical Imaging

Abstract: Medical imaging is currently being applied in artificial intelligence and big data technologies in data formats. In order for medical imaging collected from different institutions and systems to be used for artificial intelligence data, interoperability is becoming a key element. Whilst interoperability is currently guaranteed through medical data standards, compliance to personal information protection laws, and other methods, a standard solution for measurement values is deemed to be necessary in order for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, inadequate data interoperability can have a significant impact on the accuracy of AI predictions and a reference model should be embraced to establish robust data. Approaches to minimise measurement uncertainty, enable data identification, and standardise pre-existing data for research purposes are of paramount importance for data integration and enhanced AI applications in nuclear medicine [ 72 ]. Several open-source and proprietary software tools have been developed by exploiting the availability of large amounts of data for learning (open libraries, etc.).…”
Section: Limitations and Ethical Considerationsmentioning
confidence: 99%
“…However, inadequate data interoperability can have a significant impact on the accuracy of AI predictions and a reference model should be embraced to establish robust data. Approaches to minimise measurement uncertainty, enable data identification, and standardise pre-existing data for research purposes are of paramount importance for data integration and enhanced AI applications in nuclear medicine [ 72 ]. Several open-source and proprietary software tools have been developed by exploiting the availability of large amounts of data for learning (open libraries, etc.).…”
Section: Limitations and Ethical Considerationsmentioning
confidence: 99%
“…The interconnection of medical devices is emerging as a new requirement in modern medicine, and various communication standards have been proposed to achieve this (Venkatasubramanian et al, 2014). The interoperability reference model proposed by is believed to provide further developments to the artificial intelligence medical devices industry (Kwon & Yoo, 2021). In conclusion, the integration of AI in embedded systems, data analytics for real-time patient monitoring, and connectivity and interoperability among different devices have significantly advanced the impact of embedded systems in medical devices in the USA.…”
Section: Technological Advancementsmentioning
confidence: 99%

Reviewing the Impact of Embedded Systems in Medical Devices in the Usa

Sedat Sonko,
Ayodeji Matthew Monebi,
Emmanuel Augustine Etukudoh
et al. 2024
imsrj
“…Reference Healthcare issues that need to be addressed (Kwon & Yoo, 2021;Kothari et al, 2021;Usman et al, 2021;Vervoort et al, 2020) Lack of research in the healthcare domain based on blockchain interoperability, interoperability implementation of different technologies (Hasselgren et al, 2020;Kothari et al, 2021;Tandon et al, 2020) Data security, Data integrity (Sharma & Balamurugan, 2020) User authentication (Tariq et al, Furthermore, they identified user authentication, blockchains, and IoT in the drug supply chain, data exchange structure, performance, cost, efficiency, and big data of medical records, projects that are not integrated, privacy and scalability as issues that need to be addressed.…”
Section: Table 3 Research Healthcare Issuesmentioning
confidence: 99%
“…Interoperability is defined as the capability of different systems to communicate with each other without limitations (Kwon & Yoo, 2021). By exchanging data between multiple systems and allowing access to it simultaneously, blockchain technology can improve interoperability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation